2008
DOI: 10.1016/j.bone.2008.08.110
|View full text |Cite
|
Sign up to set email alerts
|

DSPP effects on in vivo bone mineralization

Abstract: Dentin sialophosphoprotein has been implicated in the mineralization process based on the defective dentin formation in Dspp null mice (Dspp-/-). Dspp is expressed at low levels in bone and Dspp-/-femurs assessed by quantitative micro-computed tomography (microCT) and Fourier transform infrared spectroscopic imaging (FTIRI) exhibit some mineral and matrix property differences from wildtype femurs in both developing and mature mice. Compared to wildtype, Dspp-/-mice initially (5 weeks) and at 7 months had signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 45 publications
2
68
0
Order By: Relevance
“…This difference in the DSPP expression levels between these non-mineralized tissues and bone was further confirmed by other approaches, such as β-galactosidase expression assays, in the Dspp knockout mice. A previous study has shown phenotypic changes in the long bone in the Dspp knockout mice (Verdelis et al 2008). The significantly higher level of DSPP expression in the salivary glands, cartilage, liver, and kidney suggests that DSPP might play important roles in these soft tissues.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This difference in the DSPP expression levels between these non-mineralized tissues and bone was further confirmed by other approaches, such as β-galactosidase expression assays, in the Dspp knockout mice. A previous study has shown phenotypic changes in the long bone in the Dspp knockout mice (Verdelis et al 2008). The significantly higher level of DSPP expression in the salivary glands, cartilage, liver, and kidney suggests that DSPP might play important roles in these soft tissues.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, DSP, a glycoprotein with little or no phosphate, was discovered in 1981 (Butler et al 1981). The importance of DSPP in biomineralization has been illustrated in human and mouse genetic studies that revealed the association of Dspp mutations or ablations with mineralization defects in the dentin and bone (Sreenath et al 2003;Verdelis et al 2008;Xiao et al 2001;Zhang X et al 2001).…”
mentioning
confidence: 99%
“…At 5 weeks of age, these mice displayed accelerated mineralisation, while at 9 months of age significant changes in bone structural properties were observed. This therefore suggests that DSPP has roles not only in the initial mineralisation of bone but also in the remodelling of the skeleton and therefore on bone turnover (Verdelis et al 2008).…”
Section: Dentin Sialophosphoproteinmentioning
confidence: 98%
“…Although originally thought to be exclusively expressed by dentin, DSPP is also expressed in bone, cementum and in non-mineralising tissues including the lung and kidney (Qin et al 2002, Baba et al 2004, Alvares et al 2006, Ogbureke & Fisher 2007, Verdelis et al 2008.…”
Section: Dentin Sialophosphoproteinmentioning
confidence: 99%
See 1 more Smart Citation